Acute Phase Reactants as Novel Predictors of Cardiovascular Disease. (6th May 2012) - Ahmed, M. S.; Jadhav, A. B.; Hassan, A.; Meng, Qing H.
Abstract : Acute phase reaction is a systemic response which usually follows a physiological condition that takes place in the beginning of an inflammatory process. This physiological change usually lasts 1-2 days. However, the systemic acute phase response usually lasts longer. The aim of this systemic response is to restore homeostasis. These events are accompanied by upregulation of some proteins (positive acute phase reactants) and downregulation of others (negative acute phase reactants) during inflammatory reactions. Cardiovascular diseases are accompanied by the elevation of several positive acute phase reactants such as C-reactive protein (CRP), serum amyloid A (SAA), fibrinogen, white blood cell count, secretory nonpancreatic phospholipase 2-II (sPLA2-II), ferritin, and ceruloplasmin. Cardiovascular disease is also accompanied by the reduction of negative acute phase reactants such as albumin, transferrin, transthyretin, retinol-binding protein, antithrombin, and transcortin. In this paper, we will be discussing the biological activity and diagnostic and prognostic values of acute phase reactants with cardiovascular importance. The potential therapeutic targets of these reactants will be also discussed.